KL-Metamatic Ghost Ship - Van Biljon, Stefan (School of Architecture, Planning and Geomatics, 2015)
The aim is to provide a comprehensive representation of the project's development from theoretical beginnings to architectural detail. The theoretical ideas underpinning my design were developed in two complementary papers, KL-Metamatic (theory) and Soft Machines (technology). Three primary interests were identified: 1. The search for a design approach aimed at a more personal experience of space. The goal was to develop a design approach that may allow occupants to rediscover their own imagination and senses through direct engagement with an atmospheric site. 2. The use of site as an a priori program. My interest in phenomenology and the subconscious was developed through a site. KL-Berth, located within Cape Town's Duncan Dock, was selected on the strength of its surprising atmospheric richness, movement and personal significance for the researcher. The letters K and L indicate the berth's position along the terminal. 3· To work in the spirit of techne. Techne, in the true sense of the word, refers to the act of uncovering the mysterious. Such experiments bear testament to a rigorous process of self-discovery through invention. This is a function of both craftsmanship and · imagination. Experimentation is emphasised over preconception.